LEWIN’S CONTRIBUTION TO STUDY GROUP: A LEARNING CHALLENGE DURING COVID-19 - Medina Simonetti, Vera Maria (RECIMA21 - Revista Científica Multidisciplinar - ISSN 2675-6218, 2022)
Significant changes are taking place in socioeconomic contexts around the world due to the covid-19 pandemic that started in 2019. Never in the history of Brazilian education there have been so many impactful moments. Schools closures were imposed due to the spread of the coronavirus. Teachers, staff, students and their respective families were perplexed by the duration of the quarantine. When it comes to public secondary education in the southeast region, pedagogical guidelines supported by remote technology were decisive for the rescue of teaching-learning process in this unusual context. Therefore, the hybrid system in basic education was adopted on a large scale. In face of it, efforts were proposed to explain the behavior of public high school youth during the implementation of study group activity, under the lens of Lewin’s field theory, using the qualitative descriptive approach. As the variables in the vital space radically changed due to the pandemic circumstance, the negative valences did interfere with the group’s behavioral response. The feelings of overload along with that of studying alone interfered with the group’s willingness to study. Concurrently, as the valences became positive with the implementation of an active pedagogical strategy, the respondents pointed out that the study group activity acted as a reinforcement of learning, as a motivator through contact with colleagues, and helped with doubts, improving comprehension of the contents. To this day, the pioneering work of Lewin demonstrates the influence of several factors interfering in the learning process in different settings.